MIP From Legionella pneumophila Influences the Phagocytosis and Chemotaxis of RAW264.7 Macrophages by Regulating the lncRNA GAS5/miR-21/SOCS6 Axis - Shen, Youfeng; Xu, Jian; Zhi, Shenshen; Wu, Wenyan; Chen, Yingying; Zhang, Qiang; Zhou, Yan; Deng, Ze; Li, Wei (Frontiers in Cellular and Infection Microbiology, 2022)
Background: The intracellular pathogen Legionella pneumophila (L. pneumophila) is a causative agent of pneumonia and does great harm to human health. These bacteria are phagocytosed by alveolar macrophages and survive to replicate within the macrophages. Despite macrophage infectivity potentiator (MIP) protein serving as an essential virulence factor during the invasion process of L. pneumophila, the regulatory mechanism of MIP protein in the process of bacterial infection to host cells is not yet completely understood. This research thus aims to explore the interaction between MIP and macrophage phagocytosis. Methods: Through the experiment of the co-culture of RAW264.7 macrophages with different concentrations of MIP, the chemotactic activity of macrophages was detected and the phagocytosis was determined by a neutral red uptake assay. The expression of long non-coding RNA (lncRNA) GAS5, microRNA-21 (miR-21), and suppressor of cytokine signaling (SOCS6) was determined by qRT-PCR. Target genes were detected by dual luciferase assay. Results: MIP could reduce the phagocytosis and improve the chemotaxis of RAW264.7 macrophages. The expression of both lncRNA GAS5 and SOCS6 was increased whereas the expression of miR-21 was decreased when macrophages were treated with MIP. Dual luciferase assay revealed that lncRNA GAS5 could interact with miR-21, and SOCS6 served as the target of miR-21. After GAS5 overexpression, the phagocytosis of RAW264.7 treated with MIP was increased whereas the chemotaxis was decreased. In contrast, the opposite results were found in RAW264.7 following GAS5 interference. Conclusions: The present results revealed that MIP could influence RAW264.7 macrophages on phagocytic and chemotactic activities through the axis of lncRNA GAS5/miR-21/SOCS6.